The Children's rights education via game-based activities: An intervention in kindergarten - Theonia Sakka; Dimitris Gouscos (Serious Games Society, 2023)
This paper presents an effort for introducing children rights to preschool students transcending conventional methods. An educational intervention was designed and developed for the introduction of preschoolers to issues of survival, development, non-discrimination and protection rights through digital games. The latter were used in online sessions, due to Covid-19 constraints. Educational effectiveness was studied through qualitative analysis of interviews with children before and after the intervention, through questionnaires regarding their degree of fun, and through the projects and the comments they produced during online sessions. Results showed that, following the intervention, individual rights occupied a more central place in the children's self-awareness. All children approached the issues of rights in relation to the improvement of the quality of life and demonstrated an ethical reasoning regarding the reciprocity of social rules. Digital games mobilized children's creative thinking, dialogue and social reflection through role-playing in distant instructional scenarios. They became useful tools as an asynchronous activity for the creative expression of social messages as well as for the interaction between children and parents. This study highlights the potential of promoting a critical approach to rights-based social issues through digital games at preschool education, as well as the need for developing serious games explicitly focused on children rights education. At the same time, further research is necessary to explore and cross-reference the views of students and parents on children rights for, and through, the use of digital games.